Clinical Pattern of Intra-cranial space occupying lesion in Tertiary Level Hospital - Datta, Ponkaj Kanti; Sutradhar, Satya Ranjan; khan, Md Nur a alam; Hossain, Mohammad Zaid; Sumon, Sultan Mahamud; Hasan, Imrul; Datta, Raj; Anwar, ASM Tanim; Islam, Rezaul; Elahi, Md Monjur E (Journal of Dhaka Medical College, 2020)
Background : The term “Intra-cranial space occupying lesion” (ICSOL) is defined as any neoplasm, benign or malignant, primary or secondary, as well as any inflammatory or parasitic mass lying within the cranial cavity. Advances in intracranial imaging have made the detection of intracranial lesions relatively accurate and enabling us to focus on the etiology of these space-occupying lesions. Many reports suggested that both incidence and pattern of intracranial space occupying lesions are subject to considerable geographic and racial variations. Knowledge of the regional peculiarities of these lesions will help in identifications of possible risk factors. Materials and Methods: This observational study was done in the department of medicine of Mymensingh medical college hospital, Bangladesh from November, 2011 to April, 2012 to evaluate the clinical pattern of ICSOL among the 75 adult admitted patients. Patient aged more than 15 years of either sex with symptoms and signs of ICSOL and at least one CT or MRI evidence in favour of diagnosis were included. Results: The highest participation (22.7%) was observed from 55-64 years age group. Mean age of the participants was 54.35±18.68 years. Neoplastic tumor was (25.8%) in 15-24 years age group and non neoplastic lesion was (31.8%) in 55-64 years age group, among participants (76.0%) came from rural areas and 24% from urban. Population regarding the occupation 30.7% were housewives, 21.3% were service holders and 20.0% are farmers. Headache was the most common symptom noted in 93.33% of patients. Nausea/ vomiting, difficulty in limb movement and imbalance were the other most common three symptoms. In this series intracerebral hemorrhage was found in 53.3% of patients, Astrocytoma was the second most common (20.0%). Meningioma was found in 8% of the participants and another 8% had metastatic lesions in their brain. There were two cases of schwanoma while tuberculoma was diagnosed in another two participants (2.7%). Conclusion: Patients with symptoms and signs of ICSOL should be dealt with great care and CT or MRI helps to evaluate them for early diagnosis and proper management. J Dhaka Medical College, Vol. 28, No.1, April, 2019, Page 17-22